Levels, variability and determinants of environmental phenols in pairs of Norwegian mothers and children. (May 2018) - Sakhi, Amrit Kaur; Sabaredzovic, Azemira; Papadopoulou, Eleni; Cequier, Enrique; Thomsen, Cathrine
Abstract: Background: Exposure to environmental phenols including parabens, bisphenols (BPs), oxybenzone/benzophenone-3 (BP-3) and triclosan (TCS) is ubiquitous. Due to evidence of their estrogenic activity, they have been considered as chemicals of concern. The exposure of the Norwegian population to these compounds is presently unknown. Aims: To measure urinary levels of twelve different environmental phenols including four emerging bisphenols: S, F, B and AF (abbreviated as BPS, BPF, BPB and BPAF, respectively) in a healthy Norwegian population. We have calculated short-term variability, estimated daily intakes and investigated important determinants of exposure. Methods: Urine samples were collected from mothers (n = 48) and their children (n = 56) during spring/summer 2012 in two counties in Norway. Results: Six environmental phenols namely methyl, ethyl and propyl paraben, BPA, BP-3 and TCS were detected in almost 100% of the urine samples. Among the emerging bisphenols, BPS was detected most frequently in the urine samples (42–48%) followed by BPF (4–15%). Parabens were positively and significantly correlated to each other in both mothers and children. Levels of parabens and BP-3 were higher in mothers compared to children. All mothers and children had lower estimated daily intakes (back calculated from the urinary concentrations) of parabens and BPA than the respective acceptable and tolerable daily intakes (ADIs and TDIs) established by the European Food Safety Authority (EFSA). Observed intraclass correlation coefficients (ICCs) indicated moderate to high reliability of spot urine measurements for all the environmental phenols (ICCs: 0.70–0.97). Use of hair products, deodorants, face and hand creams were significantly associated with higher urinary levels of parabens. Conclusions: Occurrence of environmental phenols in healthy Norwegian women and children is abundant. Among emerging bisphenols, there is widespread exposure to BPS. A single spot urine sample can be used for estimating short-term exposures of environmental phenols. Urinary levels of parabens were associated with use of PCPs. Highlights: Twelve environmental phenols were measured in Norwegian healthy mother-child pairs. Most environmental phenols showed high ICCs within 24 h. Emerging bisphenol like BPS was detected in about half of the urine samples. Urinary levels of parabens were associated with use of personal care products.